2022
DOI: 10.1002/ep.13822
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adsorptive and photocatalytic degradation properties ofFeWO4/polypyrrole nanocomposite for rose bengal and alizarin red S from liquid phase: Modeling of adsorption isotherms and kinetics data

Abstract: The FeWO4/polypyrrole nanocomposite (FeWO4/PPy NC), prepared by oxidative polymerization of pyrrole monomer with FeWO4 NPs, is used for adsorption and photocatalytic degradation of rose bengal and alizarin red S. The characterization of the nanocomposite (NC) is performed by X‐ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, energy dispersive X‐ray spectroscopy, and transmission electron microscopy. The performance of FeWO4/PPy NC is appraised under varying conditions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 56 publications
0
5
1
Order By: Relevance
“…Consistent with previous studies, both the total amount of Cr 6 + removed and its adsorption capacity increase over time. Note that the equilibrium time observed in this study is favorably shorter than those reported in some prior works, such as the 50 min observed for a kaolinite cellulose/ cobalt oxide nanocomposite [70] and FeWO 4 /Poly pyrrole nanocomposite (40 min) [71] for confiscation of contaminants.…”
Section: Nanomaterials Dosecontrasting
confidence: 55%
“…Consistent with previous studies, both the total amount of Cr 6 + removed and its adsorption capacity increase over time. Note that the equilibrium time observed in this study is favorably shorter than those reported in some prior works, such as the 50 min observed for a kaolinite cellulose/ cobalt oxide nanocomposite [70] and FeWO 4 /Poly pyrrole nanocomposite (40 min) [71] for confiscation of contaminants.…”
Section: Nanomaterials Dosecontrasting
confidence: 55%
“…The substrates used for the deposition of polypyrrole were as follows: iron [ 134 ]; iron tungstate [ 135 ]; molybdenum sulfide [ 92 ]; MWCNT [ 136 ]; silver [ 137 ]; silver manganite [ 32 ]; titanium dioxide [ 58 ]; or tungsten trioxide [ 138 ].…”
Section: Polypyrrole Photocatalystsmentioning
confidence: 99%
“…This organic compound has applications in medical diagnosis and is used to treat eczema and psoriasis. 8 However, it poses harmful effects, such as destroying the mucous membrane when inhaled and causing irritation and inflammation in the skin and eyes. 9 Likewise, methylene blue (MB) is an organic compound that reduces haemoglobin to methaemoglobin.…”
Section: Introductionmentioning
confidence: 99%